2020
DOI: 10.1002/jcla.23159
|View full text |Cite
|
Sign up to set email alerts
|

Expanded newborn screening for inborn errors of metabolism by tandem mass spectrometry in newborns from Xinxiang city in China

Abstract: Abbreviations: HPA, hyperphenylalaninemia; IEM, inborn errors of metabolism; IVA, isovaleric academia; MMA, methylmalonic academia; MS/MS, tandem mass spectrometry; MSUD, maple syrup urine disease; PCD, primary carnitine deficiency; SCAD, short-chain acyl-CoA dehydrogenase deficiency. AbstractBackground: Tandem mass spectrometry is a powerful technology available in China over the last 15 years. The development of tandem mass spectrometry had made it possible to rapidly screen newborns for inborn errors of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…There are no national detailed expanded NBS standards in China due to regional differences in the application of MSMS and lack of sufficient and valid studies. Some work has been done on the epidemiology, technical aspects and clinical validity of MS/MS screening in several provinces and cities in China, indicated that NGS combined with MS/MS is an enhanced plan for IEMs as well as disease spectrum and genetic characteristic of IEMs vary www.nature.com/scientificreports/ dramatically in different regions [9][10][11][12][13] . As far as we know this is the first single center report of the incidence, disease spectrum, and genetic characteristics of IEMs in a northwestern Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…There are no national detailed expanded NBS standards in China due to regional differences in the application of MSMS and lack of sufficient and valid studies. Some work has been done on the epidemiology, technical aspects and clinical validity of MS/MS screening in several provinces and cities in China, indicated that NGS combined with MS/MS is an enhanced plan for IEMs as well as disease spectrum and genetic characteristic of IEMs vary www.nature.com/scientificreports/ dramatically in different regions [9][10][11][12][13] . As far as we know this is the first single center report of the incidence, disease spectrum, and genetic characteristics of IEMs in a northwestern Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of NBS had significantly reduced morbidity and mortality of FAODs, but also identified a great number of mildly affected patients who might never had developed clinical symptoms throughout life, increasing the prevalence and the clinical heterogeneity of these defects [ 4 , 14 , 24 ]. In literature an incidence of 1:9000 newborns was described [ 14 ], even if a few recent studies have reported higher incidence [ 24 , 25 ]. This trend was confirmed by our study with 1 newborn in 4316.…”
Section: Discussionmentioning
confidence: 99%
“…This vital application of CMS analysis is extremely useful, and it is continually being improved. Ma et al [49] proposed a technology for the rapid determination of an extended list of metabolic diseases in dried blood spot analysis and tested it in the analysis of more than 1000 samples. A huge number of works were devoted to the early diagnosis of cancer diseases by CMS analysis based on the metabolomics.…”
Section: Metabolic Statusmentioning
confidence: 99%